Hubungan Pola Asuh Orang Tua Terhadap Kenakalan Remaja Di SMA Negeri 3 Denpasar - Ni Ketut Karisma Pebri Yani P; Claudia Wuri Prihandini; Ni Made Dwi Ayu Martini; Ketut Darmaja (STIKES Permata Nusantara Cianjur, 2025)
Adolescence is a period of psychological development during which individuals seek to discover their identity. Adolescents experience varied environments, social interactions, family dynamics, and educational settings. Negative peer influences can lead to juvenile delinquency, where parenting styles play a crucial role in shaping a child's behavior, attitudes, and personality. Proper parenting styles can reduce the likelihood of delinquent behaviors in adolescents. This study aims to determine whether there is a correlation between parenting styles and juvenile delinquency at SMA Negeri 3 Denpasar. This research employs a quantitative method with a descriptive correlation design using a cross-sectional approach, which means the study is conducted only once. The sampling technique used is purposive sampling, involving 188 respondents. Data analysis was performed using the Spearman rank test, yielding a correlation coefficient of 0.350. This indicates a moderate and positive correlation between parenting styles and juvenile delinquency, suggesting that better parenting styles are associated with decreased delinquency. Statistical tests revealed a p-value of <0.000, which is less than the significance level of α=0.05, confirming the correlation between parenting styles and juvenile delinquency at SMA Negeri 3 Denpasar.The study suggests that parents adopt parenting styles that promote moral development in children, fostering discipline and reducing delinquent behavior.